2017
DOI: 10.1080/15412555.2017.1385055
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance between Subpopulations of Regulatory T Cells in Patients with Acute Exacerbation of COPD

Abstract: Human regulatory T cells (Tregs) have been reported to be not significantly different in the peripheral blood of patients with chronic obstructive pulmonary disease (COPD) and healthy controls. Recent research has identified some new markers for Tregs and indicated that Tregs are composed of distinct subpopulations. The aim of the study was to describe the changing patterns of circulating Treg subpopulations in patients with acute exacerbation of COPD (AECOPD) and healthy controls, and to explore their potenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…Our study increased the sample size, and the results showed that the proportion of Treg cells in AECOPD and patients with SCOPD was signi cantly higher than that of HCs. Previous researchers have proposed that the imbalance of Th17/Treg cells plays an important role in the occurrence and development of COPD [32]. Our study showed that the expression of Th17 cells and Treg cells increased in AECOPD, but the increase in Th17 cells was more signi cant.…”
Section: Discussionsupporting
confidence: 45%
“…Our study increased the sample size, and the results showed that the proportion of Treg cells in AECOPD and patients with SCOPD was signi cantly higher than that of HCs. Previous researchers have proposed that the imbalance of Th17/Treg cells plays an important role in the occurrence and development of COPD [32]. Our study showed that the expression of Th17 cells and Treg cells increased in AECOPD, but the increase in Th17 cells was more signi cant.…”
Section: Discussionsupporting
confidence: 45%
“…The role of regulatory T cells (Tregs) and their different subpopulations in pulmonary diseases, has been studied extensively. Imbalances in these subpopulations have been linked to changes in clinical outcomes in different pulmonary conditions, including chronic obstructive pulmonary disease (COPD), asthma, sarcoidosis, pulmonary fibrosis, and lung cancer [1–3]. Changes in the local inflammatory milieu may add to altered Treg concentration and/or function in the airways.…”
Section: Introductionmentioning
confidence: 99%
“…In COPD, TGF-β contributes to airway remodeling through a variety of mechanisms, including induction of Treg cells and associated foxp3 mRNA expression ( Zheng et al., 2018 ) ( Yang et al., 2017 ) ( Xu et al., 2019b ) ( Chu et al., 2016 ). However, obesity reduces circulating and lung resident FOXP3+ Treg cells, amplifying airway inflammation ( Ramos-Ramírez et al., 2020 ).…”
Section: Tgf-β1 and Copdmentioning
confidence: 99%